Boron-Fluorine Photosensitizers for Photodynamic Therapy - Liang Yao; Shuzhang Xiao; Feijun Dan (Journal of Chemistry)
Photodynamic therapy (PDT) has been recognized as a promising treatment for cancers and tumors, in which photosensitizer is one of the most important issues. As a class of excellent fluorescent dyes, boron-fluorine derivatives (typically 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene, BODIPY) have preferable ability of generating singlet oxygen and have been under extensive study for PDT sensitizers. In this review, we summarize the recent progress of design and applications of boron-fluorine-based photosensitizers for PDT.